An updated identification key to the pseudoscorpions (Arachnida: Pseudoscorpiones) of the Czech Republic and Slovakia - Christophoryová, Jana; Šťáhlavský, František; Fedor, Peter (Zootaxa, 2011)
An illustrated dichotomous key is provided for the identification of adults of the pseudoscorpion species found in the Czech Republic and Slovakia, based on morphological and morphometric characters. The pseudoscorpion fauna of Slovakia includes 51 species in 7 families, and that of the Czech Republic includes 38 species in 7 families. New country records are provided: Mundochthonius carpaticus Rafalski and Microbisium brevifemoratum (Ellingsen) in the Czech Republic and Microbisium suecicum Lohmander in Slovakia.